Eddy formation through the interaction between the Leeuwin Current, Leeuwin Undercurrent and topography - Rennie, Susan; Pattiaratchi, C.; McCauley, Robert (Elsevier, 2007)
The surface and subsurface circulation off south-west Australia was simulated using the Regional Ocean Modelling System (ROMS), a primitive equation ocean model with terrain-following s-coordinates. The major currents in this region- the Leeuwin Current and Leeuwin Undercurrent- were reproduced by specifying only temperature and salinity distributions from climatology. The application of wind stress subsequent to the model reaching a quasi-steady state, resulted in the generation of the seasonal Capes Current, a northward-flowing current on the continental shelf associated with coastal upwelling. The simulated currents compared well with the observed current patterns including the location and maximum current speeds. Shelf topography variations and bottom shear, which generated vorticity, influenced eddy formation. Eddies separated from the Leeuwin Current and the Leeuwin Undercurrent, migrated westward, and exited the model domain through merging, dissipating or through an open boundary. In the model simulations, the Undercurrent produced mostly cyclonic eddies due to strong negative vorticity where the current flowed against the continental slope. The Leeuwin Current produced anticyclonic warm-core eddies initiated from the formation of meanders, which were strongest at the surface. The eddy field was dominated by anticyclonic eddies at the surface and cyclonic eddies at 500 m. The interaction between the Leeuwin Current and Leeuwin Undercurrent led to the formation of eddy pairs.